ENHANCING SERVICE DELIVERY THROUGH SERVICENOW’S VIRTUAL AGENT: A TECHNICAL OVERVIEW - Kamala Kannan Munusamy Ethirajan (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
This comprehensive technical article examines the implementation and impact of ServiceNow's Virtual Agent in modern enterprise service delivery. It explores how organizations are leveraging AI-driven virtual agents to transform their service operations across IT, HR, and customer service domains. The article covers the sophisticated architecture of Virtual Agent, including its Natural Language Understanding capabilities, conversation management, and integration features. It investigates key implementation considerations, best practices for deployment, and methods for measuring success and return on investment. Through examination of current industry data and future trends, this article demonstrates how Virtual Agent technology is revolutionizing service automation while improving operational efficiency and user satisfaction. The article also explores emerging capabilities in AI and automation that are shaping the future of virtual agent technology, providing organizations with insights for strategic planning and implementation.